IDENTIFIKASI JENIS BAMBU (Poaceae) DI HUTAN TEMBAWANG DERET JAT, DESA PERUAN DALAM KECAMATAN TAYAN HULU KABUPATEN SANGGAU - Alataris, Urbanus; Thamrin, Eddy; Herawatiningsih, Ratna (JURNAL HUTAN LESTARI, 2019)
Bamboo belongs to the Gramineae family (grasses) also called Giant Grass. Bamboos live in clumps, consisting of a number of stems (reeds) that grow gradually, starting from bamboo shoots, young and adult stems at the age of 4-6 years. The stem of this plant is cylindrical, sectioned, segmented, occasionally having massive hollow, hard-walled, in each section there are buds or branches. This study aims to find out the type and to identify the type of bamboo that is in the Tembawang Deret Jat Forest of Peruan Dalam Village in the District of Tayan Hulu, Sanggau Regency. This research will be carried out with a survey method using sampling techniques in a systematic sampling method in the form of making paths. The path used is not determined by the number of lines with a width of 20 meters and the length of the path is not determined and the distance between the lines is 50 meters. In the area of Tembawang Deret Jat Forest of Peruan Dalam Village in Tayan Hulu Subdistrict, 7 types of bamboo were found, namely Gigantochloa robusta, Gigantochloa balui, Schizostachyum zollingeri, Schizostachyum sp, Dendrocalamus asper, Schizostachyum brachycladum, Schizostachyum silicatum, and 3 bamboo genera Dendrocalamus, Gigantochloa, Schizostachyum, Schizostachyum, Schizostachyum and one Poace family.Keywords : Bamboo, Bamboo shoots, Clump, Reed, Tembawang forest.